2011
DOI: 10.3892/mmr.2011.737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bpV(pic) and bpV(phen) on H9c2 cardiomyoblasts during both hypoxia/reoxygenation and H2O2-induced injuries

Abstract: Abstract. Reactive oxygen species (ROS) are involved in myocardial injury. ROS are known to inactivate lipid phosphatase and tension homolog on chromosome 10 (PTEN), an enzyme that increases apoptosis in neonatal cardiomyocytes. BpV(pic) and bpV(phen), two bisperoxovanadium molecules and PTEN inhibitors, may be involved in limiting myocardial infarction. To compare the protective effects of bpV(pic) and bpV(phen) on ROS-induced cardiomyocyte injury and their possible mechanisms, we selected two popular models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…To determine if increased activity of Cdc42 might be controlled by PTEN activation, Cdc42 activity was analysed in PMVECs after treatment with BpV(pic), an inhibitor of PTEN by blocking the phosphorylation of PTEN. 25 First, we confirmed that BpV(pic) treatment successfully inhibited the phosphorylation of PTEN (P < 0.05) in PMVECs (Figure 5C and D). Consistent with our hypothesis, the levels of activated Cdc42 diminished in the CBDL group (P < 0.05) (Figure 5E and F).…”
Section: Activated Pten Regulates the Abnormal Activation Of Cdc42 In...supporting
confidence: 64%
“…To determine if increased activity of Cdc42 might be controlled by PTEN activation, Cdc42 activity was analysed in PMVECs after treatment with BpV(pic), an inhibitor of PTEN by blocking the phosphorylation of PTEN. 25 First, we confirmed that BpV(pic) treatment successfully inhibited the phosphorylation of PTEN (P < 0.05) in PMVECs (Figure 5C and D). Consistent with our hypothesis, the levels of activated Cdc42 diminished in the CBDL group (P < 0.05) (Figure 5E and F).…”
Section: Activated Pten Regulates the Abnormal Activation Of Cdc42 In...supporting
confidence: 64%
“… 36 38 The PTEN inhibitor bpv(Pic) was reported to promote neurite outgrowth, 39 bpv(Pic) provides neuroprotection against oxidative stress and neurotoxicity in Alzheimer's disease, 40 and bpv(Pic) and bpv(Phen) have protective effects on oxidative stress-induced cardiomyocyte injury. 41 In addition, PTEN inhibition not only functions as a neuroprotective factor in the nervous system, but also has many functions in wound repair, such as regulating the migration of a variety of epithelial cells. PTEN inhibitors were associated with wound healing in many models, PTEN inhibition improves wound healing in lung epithelia or corneal epithelium injury by enhancing migration, 18 , 42 bpv(Pic) promotes proliferation and alleviates senescence to stimulate skin renewal, 43 and bpv (Phen) reverses HG-induced apoptosis in human umbilical vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, more indirect methods like assessing the phosphorylation state of Akt/PKB were used, whereas we directly monitored PTEN's substrate PI(3,4,5)P 3 to determine the effect of these inhibitors in living cells. The bpV compounds have been used to study the involvement of PTEN in signaling, proliferation, apoptosis, and neurogenesis (Band et al, 1997 ; Batty et al, 2007 ; Pi et al, 2012 ; Tian et al, 2012 ; Becker et al, 2013 ); however, higher concentrations (200 nM–100 μM) were required. We found comparable concentrations to effectively inhibit PTEN activity in our live cell assay.…”
Section: Discussionmentioning
confidence: 99%